2020
DOI: 10.1097/dcr.0000000000001625
|View full text |Cite
|
Sign up to set email alerts
|

Colon and Rectal Surgery Robotic Training Programs: An Evaluation of Gender Disparities

Abstract: BACKGROUND: Female surgeons are subjected to implicit bias throughout their careers. The evaluation of gender bias in training is warranted with increasing numbers of female trainees in colon and rectal surgery. OBJECTIVE: This study aimed to evaluate gender bias in colon and rectal surgery training program operative experience. DESIGN: This is a retrospective cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…Women trainees were reported to be less likely to have children (2.5% female vs 40% male, P =0.0215 in the study by Rogers et al37; 19% female vs 49% male, P <0.001 in the study by Stephens et al39). When considering training opportunities, Foley et al40 reported significant differences in average console participation between sexes (53.5% female and 61.7% male, P <0.001); male attending surgeons were reported to provide female trainees with less console participation (52.1% vs 59.7%, P <0.001), while female attending surgeons provided the same amount of console participation to female and male trainees (63.3% vs 61.8%, P =0.62).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women trainees were reported to be less likely to have children (2.5% female vs 40% male, P =0.0215 in the study by Rogers et al37; 19% female vs 49% male, P <0.001 in the study by Stephens et al39). When considering training opportunities, Foley et al40 reported significant differences in average console participation between sexes (53.5% female and 61.7% male, P <0.001); male attending surgeons were reported to provide female trainees with less console participation (52.1% vs 59.7%, P <0.001), while female attending surgeons provided the same amount of console participation to female and male trainees (63.3% vs 61.8%, P =0.62).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 5 papers [37][38][39][40][41] reported significant differences between male and female trainees both in private and working environments. Women trainees were reported to be less likely to have children (2.5% female vs 40% male, P = 0.0215 in the study by Rogers et al 37 ; 19% female vs 49% male, P < 0.001 in the study by Stephens et al 39 ).…”
Section: Surgical Trainingmentioning
confidence: 99%
“…Secondly, previous reports have shown a bias in the number of surgical cases assigned to male versus female surgeons during their training 30. Foley and colleagues reported gender differences in the experience with robotic surgery in colorectal surgery training programmes, with female trainees having fewer opportunities to participate in the use of consoles and to complete the procedures 31. They also reported that male supervisors provided fewer opportunities for console participation to female residents than to male residents, but female supervisors provided the same number of console use opportunities to both female and male trainees.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Furthermore, female residents are significantly underrepresented among award recipients in general surgery residency programs. 28 In a study on gender disparity in robotic surgical experience in a colorectal surgery training program, 29 female residents had lower rates of console participation and fewer opportunities to complete total mesorectal excision than male residents. Furthermore, female attending surgeons offered equal opportunities for surgical experience to male and female residents, but male attending surgeons offered fewer opportunities to female residents.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, female attending surgeons offered equal opportunities for surgical experience to male and female residents, but male attending surgeons offered fewer opportunities to female residents. 29 The majority of attending surgeons in Japan are male, and a prevailing gender bias among them may influence the surgical experience of residents.…”
Section: Discussionmentioning
confidence: 99%